The Relationships among Target Cost Management, Cost Advantage, Customer Satisfaction and Sustainable Competitive Advantage of Micro, Small and Medium-sized Enterprises (MSMEs) in Thailand - ถาพยอม อนุชา (วารสารการบัญชีและการจัดการ, 2022)
The purpose of this research is to examine the effect of target cost management on sustainable competitive. Data was collected from 400 Micro, Small and Medium-sized Enterprises in Thailand by questionnaire mail survey. To test the research relationships, structural equation modeling (SEM) as a statistical technique is employed. The results reveal that target cost management has a significant positive association with cost advantage, customer satisfaction and sustainable competitive. Likewise, cost advantage is positively related to customer satisfaction. Furthermore, customer satisfaction has a positive influence on sustainable competitive. To improve and increase the benefits of target cost management, executives need to determine how to implement target cost management in a business, link this strategic operational tool to cost advantages, customer satisfaction and sustainable competitive, and manage and deal with competitive markets and environments. Therefore, firms need to create business vision, be aware of competitive forces and offer organizational changes through outstanding restructuring, redesign and re-engineering their practices, operations, functions, and strategies in order to meet target cost management implementation requirements.